Pregnancy loss and its predictors among ever-pregnant women in Sub-Saharan Africa: Multilevel mixed effect negative binomial regression. - Abel Endawkie; Yawkal Tsega (PLOS Global Public Health)
Background Pregnancy loss is a significant maternal health issue in Sub-Saharan Africa. Africa has the highest rates of stillbirths globally, with an estimated 2.7 million stillbirths occurring each year on the continent. The pregnancy loss data are underreported and inconsistently recorded in Sub-Saharan Africa. Therefore, this study aimed to determine the number of pregnancy loss and its predictors among ever-pregnant women in Sub-Saharan Africa using a recent round of demographic and health survey (DHS) data. Method A secondary data analysis was conducted among 235,086 weighted ever-pregnant women in Sub-Saharan Africa using a recent round of DHS data from 2015-2023. Multilevel mixed effect negative binomial regression was conducted. An adjusted incidence rate ratio (AIRR) with a 95% confidence interval (CI) was reported. Result The median number of pregnancy loss in Sub-Saharan Africa is 2.67, 95%CI (2.64, 2.69). A one-year increase in maternal age [AIRR= 1.05, 95%CI (1.06, 1.07)], primary educational status of the mother [AIRR = 1.10, 95% CI (1.01, 1.22)], women with a partner who has higher education [AIRR= 1.18, 95% CI (1.04, 1.39)], a higher number of under-five children [AIRR =0.95, 95% CI (0.91,0.99)], women have ever pregnant in Cote'divore [AIRR 1.76, 95% CI (1.6, 2)] are associated with the number of pregnancy loss. Conclusion The findings indicate that there are three pregnancy losses among ever-pregnant women in Sub-Saharan Africa. Notably, a one-year increase in maternal age and higher education levels for both mothers and their partners are linked to an increased risk of pregnancy loss. In contrast, mothers with multiple children generally experience lower rates of loss. Therefore, policy interventions should address the heightened risk of pregnancy loss linked to advancing maternal age and higher education levels for both mothers and their partners. This can be achieved by supporting programs that educate prospective parents about the effects of maternal age on pregnancy outcomes. Furthermore, promoting flexible educational pathways and providing career support can encourage healthier timing for pregnancies. Additionally, initiatives that support families and promote larger family sizes may help reduce pregnancy loss rates in Sub-Saharan Africa.